Creativity and Crime 2013
DOI: 10.1017/cbo9781139176118.002
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and crime

Abstract: A battery of thirteen tests, six ' convergent ' and seven ' divergent,' was administered to 320 Grade Seven children and the ' divergent ' tests scored for originality. Correlations were then subjected to principal axis factor analysis. The results indicated that the two largest factors were defined by ' convergent ' tests and ' divergent ' tests, respectively. These factors were subjected to both orthogonal and oblique rotations and it was found that, although the ' divergent ' tests indicated a separate fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…H. Cropley and A. J. Cropley (2013) argued that creativity theory could also be applied with profit in other areas of real life (they focused on the apparently remote domain of combating crime), but is largely ignored, for the reason just given (conflation of creativity with the arts). D. H. Cropley, A. J. Cropley, Kaufman, and Runco (2010) also complained that there is a strong tendency to regard creativity as unquestionably good because of its association with the generation of aesthetic beauty, whereas more realistic observation shows that it has a substantial dark side.…”
Section: University Of Hamburg Germanymentioning
confidence: 99%
“…H. Cropley and A. J. Cropley (2013) argued that creativity theory could also be applied with profit in other areas of real life (they focused on the apparently remote domain of combating crime), but is largely ignored, for the reason just given (conflation of creativity with the arts). D. H. Cropley, A. J. Cropley, Kaufman, and Runco (2010) also complained that there is a strong tendency to regard creativity as unquestionably good because of its association with the generation of aesthetic beauty, whereas more realistic observation shows that it has a substantial dark side.…”
Section: University Of Hamburg Germanymentioning
confidence: 99%
“…Both circles and squares have been commonly used in many different types of psychology experiments, and none of the studies have reported any difficulties in identifying or recognizing the shapes. For example, circles have been included in many tests aimed at investigating aspects of creativity (e.g., Cropley, 1967Cropley, , 1972French, Ekstrom, & Price, 1963;Torrance, 1962Torrance, , 1966Torrance, , 1974Torrance, , 1984. Both shapes have also been used to test if they affect variety-seeking behavior in consumers (Maimaran & Wheeler, 2008) and whether or not they affect mood (Hevner, 1935).…”
Section: Methodsmentioning
confidence: 99%
“…His first book on the subject, appropriately entitled Creativity (A. J. Cropley, 1968), masks the fact that his research in creativity spanned divergent thinking in science, intelligence, mental health, creativity tests, and even biochemistry (A. J. Cropley, Cassell, & Maslany, 1970).…”
Section: From School Teacher To Creativity Researchermentioning
confidence: 99%
“…I was, however, impressed by the fact that Arthur had written books and that one in particular, Creativity (A. J. Cropley, 1968) seemed to be a big deal. Once, when we were travelling through London in the late 1970s, we went to the famous Foyles bookstore on Charing Cross Road, and Arthur showed us a copy of Creativity on their shelves.…”
Section: Creativity Lifelong Learning and Giftednessmentioning
confidence: 99%